Pengaruh Kepemilikan Asing dan Nilai Tukar Terhadap Keputusan Transfer Pricing Pada Perusahaan Manufaktur - Fathinus Syafrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to examine the effect of foreign ownership and exchange rates on transfer pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of research used in this research is quantitative with a quantitative descriptive approach. The data used in this study is secondary data in the form of audited financial reports in the form of annual reports of manufacturing companies that are contained in Indonesia Securities for 2017-2021. The data analysis method used is a quantitative analysis method that is measured on a numerical scale or numbers. The results of this study are first, foreign ownership does not affect the company's transfer pricing decisions. These results indicate that foreign controlling shareholders do not use their control rights to instruct management in carrying out transfer pricing. Second, that the exchange rate has no effect on the company's transfer pricing decisions. The average sample company exchange rate is -18.62%, meaning that many sample companies experience exchange rate losses or in other words changes in exchange rates do not affect the company's transfer pricing decisions. Therefore, the second hypothesis is rejected.